2020
DOI: 10.3390/pharmaceutics12080761
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Thymoquinone-Loaded Soy-Phospholipid-Based Phytosomes Exhibit Anticancer Potential against Human Lung Cancer Cells

Abstract: Thymoquinone (TQ), a natural polyphenol, has been associated with various pharmacological responses; however, low bioavailability of TQ limits its clinical application. Thus, a novel phytosomal delivery system of TQ-Phospholipon® 90H complex (TQ-phytosome) was developed by refluxing combined with anti-solvent precipitation. This TQ delivery system was optimized by a three-factor, three-level Box-Behnken design. The optimized TQ-phytosome size was (45.59 ± 1.82 nm) and the vesicle size was confirmed by transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 40 publications
(60 reference statements)
3
40
0
Order By: Relevance
“… 7 Since For hundreds of years, thymoquinone (TQ) has been commonly used for conditions ranging from a simple migraine to illnesses such as obesity, asthma, gastrointestinal problems, menstruation and lactation. 8 , 9 TQ is a member of the Ranunculaceae family, rising on Mediterranean coastal plants. Almond oil (AO) is a colloidal liquid containing proteins, minerals and vitamins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Since For hundreds of years, thymoquinone (TQ) has been commonly used for conditions ranging from a simple migraine to illnesses such as obesity, asthma, gastrointestinal problems, menstruation and lactation. 8 , 9 TQ is a member of the Ranunculaceae family, rising on Mediterranean coastal plants. Almond oil (AO) is a colloidal liquid containing proteins, minerals and vitamins.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that oxygen radicals may contribute to the formation of ethanol-induced gastric mucosal lesions, and antioxidants are protective against the damage caused by these oxidants. 7 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…It also showed the ability to suppress the ERK1/2 signaling pathway, which inhibited the migration and invasion of A549 cells [ 66 ]. TQ combined with a developed delivery system (TQ-phytosome) induced apoptosis at 4.31 ± 2.21 µM via the activation of caspase-3 and generation of reactive oxygen species (ROS), in addition to accumulating cells on G2-M and pre-G1 phases in the A549 cell line [ 67 ]. TQ enhanced apoptosis by increasing the Bax/Bcl2 ratio and upregulating the p53 expression in A549 cells [ 11 ] and mice [ 68 ].…”
Section: Anti-cancer Effects Of Tqmentioning
confidence: 99%
“…The analysis of variance (ANOVA) was used to statistically investigate the data to evaluate the significance of the studied variables. Interactions between the independent variables were assessed from the generated contour plots and interaction plots [ 25 ]. The best fitting model was selected based on an adequate precision ratio and the predicted and adjusted determination coefficients for the measured response.…”
Section: Methodsmentioning
confidence: 99%